The Production of Smalt and Other Cobalt Compounds at the Blaafarveværket, Modum, Norway - Bjørnland, Lasse Hermansen; Degryse, Patrick; Schibille, Nadine; Eremin, Katherine; Walton, Marc Sebastian; Gratuze, Bernard; Braekmans, Dennis; Shortland, Andrew J. (​Forensic Archaeology, Anthropology and Ecology, 2024)
Forensic analysis of fine art and objet d’art uses accurately determined pigment compositions to confirm or deny provenance, dating and attribution. Some of the most important pigments in this respect are those associated with cobalt. The Blaafarveværket, or Blue Colour Works, based near Modum in Norway, was a producer of cobalt products (especially smalt and zaffre) during the eighteenth and nineteenth, exploiting local cobalt ores and other raw materials locally sourced and brought in from more distant areas. century. The Blue Colour Works is now a museum and study of its archive has detailed type and quantity of its production, showing that it was perhaps the most important producer of cobalt products in the early nineteenth century, and the largest mining operation in Norway. The archive gives details of the production processes for some of the products and shows that these processes changed through time. The museum preserves samples of different parts of the intermediate and end products, showing that the output was a smalt very low in manganese and zinc, with some nickel, significant iron and arsenic and relatively raised bismuth and uranium contents. REE element analysis combined with lead isotopes shows that different sources of silica were probably used, since both are quite variable, supporting archive suggestions that external sources of silica and plant ash were employed on occasions.